mHealth Applications to Monitor Lifestyle Behaviors and Circadian Rhythm in Clinical Settings: Current Perspective and Future Directions - Rosa, Iolanda; Lages, Marlene; Grilo, Carlos; Barros, Renata; Guarino, Maria P. (Frontiers in Public Health, 2022)
Nutritional habits and behaviors have a significant impact on human health and are often linked to the risk of developing chronic metabolic diseases. Most studies in this area focus solely on the quality and quantity of food consumed, without taking meal timing into account. Chrononutrition is an emerging field that aims to address these shortcomings by relating nutritional health concerns to the human body's circadian rhythm. The NutriClock study arose from this concept and aims to find the optimal meal schedule for prediabetic patients, considering their circadian rhythm and individual chronotype. The study's primary goal is to evaluate the impact of planning a meal intake schedule, based on the chronotype, on metabolic disease progression and severity. Herein we describe a developed software platform that serves as the technological foundation for the study. The system consists of three applications: a backoffice for viewing and managing information; a mobile application for patient data entry; and a backend for encapsulating business rules, accessing the database, and communicating with the client applications. The NutriClock platform was tested using manual, automated, and usability tests, which helped to fix some bugs and improve the user interface, with a focus on maximizing the naturalness of interactions.